Relationship between environmental, social, and governance (ESG) practices and business performance: empirical evidence for S&P 500 companies - Flores, Alejandro (2025)
This study analyzes the relationship between ESG practices and business performance in companies belonging to the S&P 500 index during the period 2015-2024, using panel data models with fixed effects. A negative effect of ESG on market capitalization is observed, while no significant effects are identified on return on assets. By conducting a heterogeneity analysis through sectoral interactions and quintile segmentation, it is contrasted that the effect is not uniform. These findings suggest that the effects of ESG depend on the main activity and market capitalization, highlighting benefits in technological companies and costs in industrial companies. Likewise, in the case of companies with lower capitalization, the effect turns out to be positive in the most representative activities of the sample. Our recommendations emphasize the need for companies to adopt differentiated ESG strategies, considering their sectoral context and market value.